Social media, efficacy, and non-normative collective action in Chile, Colombia, and Peru - Ruiz Dodobara, Fernando Gabriel (2025)
In recent years, political instability in South American countries has led to an increase in violent collective actions. While extensive research has examined normative collective action, fewer studies have investigated its non-normative forms, particularly regarding the comparison of the predictive role of participative and group efficacy in non-normative collective behavior. By analyzing the dynamics between social media, efficacy, and non-normative collective behavior, this study aims to provide insights into the indirect effect of group and participative efficacy in the relationship between political social media use and non-normative collective action. Structural Equation Modeling analysis was done using a sample of 1979 participants from Chile, Colombia, and Peru. Participative efficacy was found to mediate the relationship between political social media use and non-normative collective action in all three countries, while only in Peru group efficacy mediated this relationship, with a negative effect. The authors concluded that non-normative collective action is better predicted by individual perceptions such as participative efficacy.